Poly(ADP‐ribose)polymerase 1 inhibition protects against age‐dependent endothelial dysfunction. (December 2015) - Zhang, Guang‐hao; Chao, Min; Hui, Long‐hua; Xu, Dong Ling; Cai, We‐li; Zheng, Jie; Gao, Min; Zhang, Ming‐xiang; Wang, Juan; Lu, Qing‐hua
Summary: Age‐related endothelial dysfunction is closely associated with the local production of reactive oxygen species (ROS) within and in the vicinity of the vascular endothelium. Oxidant‐induced DNA damage can activate the nuclear enzyme poly(ADP‐ribose) polymerase 1 (PARP‐1), leading to endothelial dysfunction in various pathophysiological conditions. The present study aimed to investigate the role of PARP‐1 in age‐dependent changes in endothelial cell function and its underlying mechanism. Wild‐type (WT) and PARP‐1 −/− mice were divided into young (2 months) and old (12 months) groups. Isolated aortic rings were suspended to record isometric tension to assess endothelial function. Nitric oxide (NO) production and content in plasma were detected by spectrophotometry. Superoxide ( O 2 − production was detected by dihydroethidium. Expression of PARP‐1, endothelial nitric oxide synthase (eNOS), induced nitric oxide synthase (iNOS), and arginase‐2 (Arg2) was assessed by western blot analysis. Endothelium‐dependent relaxation in response to acetylcholine was lost in old WT, but not PARP‐1 −/−, mice. Endothelium‐independent vasodilation was not impaired in aging mice. Production of O 2 − was greater in aging WT mice than young or aging PARP‐1 −/− mice. eNOS expression was not affected by aging in WT or PARP‐1 −/− mice, but p‐eNOS expression decreased and iNOS and Arg2 levels were upregulated only in aging WT mice. In conclusion, PARP‐1 inhibition may protect against age‐dependent endothelial dysfunction, potentially by regulating NO bioavailability via iNOS. Inhibition of PARP‐1 may help in vascular aging prevention.